2013
DOI: 10.1158/0008-5472.can-13-0344
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab Attenuates Its Cytotoxic and Radiosensitizing Potential by Inducing Fibronectin Biosynthesis

Abstract: Inherent and acquired resistance to targeted therapeutics continues to emerge as a major clinical obstacle. For example, resistance to EGF receptor targeting occurs commonly, more so than was expected, on the basis of preclinical work. Given emerging evidence that cancer cell-substrate interactions are important determinants of therapeutic sensitivity, we examined the impact of cell-fibronectin interactions on the efficacy of the EGF receptor antibody cetuximab, which is used widely for lung cancer treatment. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 47 publications
3
42
0
Order By: Relevance
“…10 In brief, 5 × 10 5 cells were embedded in 0.5 mg/ml lrECM. At 24 h after seeding, cells were treated with AIIB2 or IgG#1 (10 μg/ml), irradiated (6 Gy Table 2).…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In brief, 5 × 10 5 cells were embedded in 0.5 mg/ml lrECM. At 24 h after seeding, cells were treated with AIIB2 or IgG#1 (10 μg/ml), irradiated (6 Gy Table 2).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…[3][4][5][6] We and other groups have demonstrated enhanced tumor cell sensitivity to radiotherapy, chemotherapy and molecular drugs as a result of antibody-mediated β1 integrin targeting in various preclinical cancer models including head and neck, lung, brain, breast and leukemia. [7][8][9][10][11][12] Integrins are transmembrane cell adhesion receptors for ECM proteins. 18 α and 8 β integrin subunits can form 24 different α/β integrin heterodimers by non-covalent binding.…”
Section: Introductionmentioning
confidence: 99%
“…For immunofluorescence staining, cells were prepared, stained and images were acquired with the LSM meta 510 (Zeiss) as published [28]. Human tissues were obtained from pathology archival material in a blinded fashion as approved by the ethics committee of the Dresden University of Technology (Germany).…”
Section: Immunofluorescence Staining and Histologymentioning
confidence: 99%
“…Numerous cytoplasmic protein kinases, including focal adhesion kinase (FAK), and adapter proteins facilitate downstream integrin signaling to control cell survival, therapy resistance and metastasis. In addition to hampering invasion, we and others have demonstrated that b1 integrin targeting enhances radiochemosensitivity in head and neck cancer, glioblastoma, lung cancer, pancreatic cancer, breast cancer and leukemia [10][11][12][13][14][15][16][17]. In head and neck cancers, simultaneous b1 integrin/EGFR targeting elicited stronger radiosensitization than monotherapies [18].…”
mentioning
confidence: 89%